Rehabilitation strategies and neurological consequences in patients with COVID-19: part I - Cetisli-Korkmaz, Nilufer; Bilek, Furkan; Can-Akman, Tuba; Baskan, Emre; Keser, Ilke; Dogru-Huzmeli, Esra; Kilinc, Buse (Taylor & Francis Ltd, 2021)
Background: The 2019 novel coronavirus disease (COVID-19) pandemic has triggered a devastating effect worldwide. In addition to cardiovascular, pulmonary, and musculoskeletal deconditioning, reports of neurological consequences (e.g. stroke, critical illness polyneuropathy, myopathy, vertigo, headaches, facial palsy, and delirium) are growing increasingly common. Objectives: Part I of this review of rehabilitation strategies and neurological consequences in patients with COVID-19 sought to consider potential rehabilitation strategies for managing the emerging neurological consequences of COVID-19. Methods: An exploratory review was conducted that comprised a narrative synthesis in two parts. Part I focused on neurological consequences and physiotherapy and rehabilitation approaches. Part II focused on the general principles of rehabilitation interventions and precautions that should be considered. Literature on the use of the neurorehabilitation approaches was also included in the review. Results: Rehabilitation services include inpatient and outpatient rehabilitation services. With respect to the recovery of mobility and function, an interdisciplinary approach was generally involved. Conclusions: A thorough assessment and the development of an individualized, progressive treatment and rehabilitation plan should be implemented by focusing on existing function, any disabilities, the desire to return to participation in society, and maximizing function and quality of life. It should be noted that neurorehabilitation should not be delayed and be completed for all patients with COVID-19 of all levels in need.
Keywords: COVID-19; neurological consequences; physiotherapy and rehabilitation; neurorehabilitation; exercise; telerehabilitation